Appeal references and their impact on determining the qualitative jurisdiction of administrative courts (Journal of Humanities and Social Sciences Research, 2023)
The administrative judiciary arose in Iraq with the issuance of Law No. 106 of 1989. The administrative judiciary became specialized in adjudicating disputes in which the administration is a party. Since that date, a conflict of positive and negative jurisdiction has arisen between the civil and administrative courts, which resulted in the establishment of the authority to appoint the reference. It is made up of six members headed by the President of the Court of Cassation, which sparked controversy regarding the impartiality of this body’s decision. This body is concerned with looking into conflicts of jurisdiction that may occur between a civil court and the Administrative Court, while the Supreme Administrative Court is competent to settle jurisdictional conflicts between the State Employees Judicial Court and the Administrative Court, in contrast to the Egyptian judiciary, which gave the authority to settle disputes in administrative disputes to the Constitutional Court. The Supreme Court, while the jurisdiction of adjudicating the conflict of jurisdiction between the civil judiciary was granted to the Court of Cassation.